The GATA transcription factor ELT-2 modulates both the expression and methyltransferase activity of PRMT-1 in Caenorhabditis elegans. (18th January 2018) - Araoi, Sho; Daitoku, Hiroaki; Yokoyama, Atsuko; Kako, Koichiro; Hirota, Keiko; Fukamizu, Akiyoshi
Abstract: Protein arginine methyltransferase 1 (PRMT1) catalyzes asymmetric arginine dimethylation of cellular proteins and thus modulates various biological processes, including gene regulation, RNA metabolism, cell signaling and DNA repair. Since prmt-1 null mutant completely abolishes asymmetric dimethylarginine in C. elegans, PRMT-1 is thought to play a crucial role in determining levels of asymmetric arginine dimethylation. However, the mechanism underlying the regulation of PRMT-1 activity remains largely unknown. Here, we explored for transcription factors that induce the expression of PRMT-1 by an RNAi screen using transgenic C. elegans harbouring prmt-1 promoter upstream of gfp . Of 529 clones, we identify a GATA transcription factor elt-2 as a positive regulator of Pprmt-1:: gfp expression and show that elt-2 RNAi decreases endogenous PRMT-1 expression at mRNA and protein levels. Nevertheless, surprisingly arginine methylation levels are increased when elt-2 is silenced, implying that erythroid-like transcription factor (ELT)-2 may also have ability to inhibit methyltransferase activity of PRMT-1. Supporting this idea, GST pull-down and co-immunoprecipitation assays demonstrate the interaction between ELT-2 and PRMT-1. Furthermore, we find that ELT-2 interferes with PRMT-1-induced arginine methylation in a dose-dependent manner. Collectively, our results illustrate the two modes of PRMT-1 regulation, which could determine the levels of asymmetric arginine dimethylation in C. elegans .